BECN1-dependent CASP2 incomplete autophagy induction by binding to rabies virus phosphoprotein. Issue 4 (3rd April 2017) - Liu, Juan; Wang, Hailong; Gu, Jinyan; Deng, Tingjuan; Yuan, Zhuangchuan; Hu, Boli; Xu, Yunbin; Yan, Yan; Zan, Jie; Liao, Min; DiCaprio, Erin; Li, Jianrong; et al.
ABSTRACT: Autophagy is an essential component of host immunity and used by viruses for survival. However, the autophagy signaling pathways involved in virus replication are poorly documented. Here, we observed that rabies virus (RABV) infection triggered intracellular autophagosome accumulation and results in incomplete autophagy by inhibiting autophagy flux. Subsequently, we found that RABV infection induced the reduction of CASP2/caspase 2 and the activation of AMP-activated protein kinase (AMPK)-AKT-MTOR (mechanistic target of rapamycin) and AMPK-MAPK (mitogen-activated protein kinase) pathways. Further investigation revealed that BECN1/Beclin 1 binding to viral phosphoprotein (P) induced an incomplete autophagy via activating the pathways CASP2-AMPK-AKT-MTOR and CASP2-AMPK-MAPK by decreasing CASP2. Taken together, our data first reveals a crosstalk of BECN1 and CASP2-dependent autophagy pathways by RABV infection.